I love Cayambe: City Branding Campaign - Calderón Garrido, Zoila Lourdes (2020)
The late interest of Ecuador to work on a brand caused that smaller cities also delay their own brand. This did not favor their tourism development, as well as the growth of investment and business. This article is a diagnosis of the current tourist situation of Cayambe, as of other references, proposing the creation of the city branding. Regarding its positioning, a visual advertising strategy that impacts the objectives of the city and its inhabitants through transmedia tactics, is suggested.